Legal Certainty Aspects in Regulation of the Attorney General Number 15 of 2020 Concerning Termination of Prosecution Based on Restorative Justice - Sardjana Orba Manullang; Rai Iqsandri; Mawarni Fatma; Avelia Rahmah Y. Mantali (IHSA Institute, 2022)
There have been many sharp criticisms regarding law enforcement by law enforcement officials where small cases that could be resolved through peaceful efforts ended up in court. In 2020, the Attorney General issued Prosecutor Regulation Number 15 of 2020 concerning termination of prosecution. It is necessary to pay attention to the legal certainty aspect of the regulation when it is implemented. This study aims to analyze the aspect of legal certainty in the Prosecutor's Regulation Number 15 of 2020 concerning termination of prosecution based on restorative justice. Study this law uses a normative juridical approach Statutory Approach, the